2016
DOI: 10.5137/1019-5149.jtn.16659-15.1
|View full text |Cite
|
Sign up to set email alerts
|

The platelet indices in diagnosis of ventriculoperitoneal shunt infection in children.

Abstract: Our results suggest that MPV and PDW can be used for the diagnosis of VPSI in children with an accuracy of at least 75%. Moreover, MPV"s specificity is higher than the other platelet parameters and leucocyte count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…In the literature, we found only one study that examined the platelet parameters in VP shunt infection. Çelik and colleagues, as in our study similar, have found that despite the increased platelet count, MPV was found to be lower than the control group (31). In a study evaluating adult patients with bacterial meningitis and tuberculosis meningitis, platelet count was lower and MPV was higher in patients with bacterial meningitis compared to patients with tuberculous meningitis and healthy control group (32).…”
Section: Discussionsupporting
confidence: 70%
“…In the literature, we found only one study that examined the platelet parameters in VP shunt infection. Çelik and colleagues, as in our study similar, have found that despite the increased platelet count, MPV was found to be lower than the control group (31). In a study evaluating adult patients with bacterial meningitis and tuberculosis meningitis, platelet count was lower and MPV was higher in patients with bacterial meningitis compared to patients with tuberculous meningitis and healthy control group (32).…”
Section: Discussionsupporting
confidence: 70%
“…Orthopedists often pay attention to white blood cell (WBC) count and neutrophil count in CBC to diagnose or monitor infections; however, their sensitivity and specificity are very low in fracture patients 2,3. Besides WBC count and neutrophil count, recent studies gradually focus on the role of platelet indices including platelet count (PLT), mean platelet volume (MPV), and platelet distribution width (PDW) in diagnosing infections such as acute appendicitis, ventriculo-peritoneal shunt infection, and urinary tract infection 47. To our knowledge, there are no studies conducted examining the diagnosis of DSSI after ORIF for traumatic limb fractures using platelet indices.…”
Section: Introductionmentioning
confidence: 99%
“…14 There have been studies of children in respect of the diagnostic and follow-up value of PDW in many diseases such as immunodeficiency disease, ventriculoperitoneal shunt infection, congenital heart disease, pulmonary arterial hypertension, acute ischemic stroke, and neonatal sepsis. [14][15][16][17][18] Some studies in the literature have shown conflicting results about the supportive value of PDW in the diagnosis of AA . While some of these studies have demonstrated a correlation between PDW and AA, others have reported no change in the value of PDW.…”
Section: Discussionmentioning
confidence: 99%